Guidelines for practical work on the topic "Stress and its prevention" - Vambol, Sergij Oleksandrovich; Mezentseva, Iryna Oleksandrivna (National Technical University "Kharkiv Polytechnic Institute", 2025)
Acquisition by students of practical knowledge on definition of types of temperaments of people influencing development of stress, and practical skills of prevention of its negative consequences by means of autogenic training which allows to remove a stressful condition promoting health and working capacity in ordinary and extreme situations.
Keywords: guidelines; temperament; choleric; sanguine; psychology; mental tension; autogenic training; melancholic; phlegmatic